Influencing factors of carbonyl compounds and other VOCs in commercial airliner cabins: On‐board investigation of 56 flights. (9th July 2021) - Yin, Yihui; He, Junzhou; Pei, Jingjing; Yang, Xudong; Sun, Yuexia; Cui, Xikang; Lin, Chao‐Hsin; Wei, Daniel; Chen, Qingyan
Abstract: Volatile organic compounds (VOCs) as a non‐negligible aircraft cabin air quality (CAQ) factor influence the health and comfort of passengers and crew members. On‐board measurements of carbonyls (short‐chain (C1 ‐C6 )) and other volatile organic compounds (VOCs, long‐chain (C6 ‐C16 )) with a total of 350 samples were conducted in 56 commercial airliner cabins covering 8 aircraft models in this study. The mean concentration for each individual carbonyl compound was between 0.3 and 8.3 μg/m 3 (except for acrolein & acetone, average = 20.7 μg/m 3 ) similar to the mean concentrations of other highly detected VOCs (long‐chain (C6 ‐C16 ), 97% of which ranged in 0–10 μg/m 3 ) in aircraft cabins. Formaldehyde concentrations in flights were significantly lower than in residential buildings, where construction materials are known formaldehyde sources. Acetone is a VOC emitted by humans, and its concentration in flights was similar to that in other high‐occupant density transportation vehicles. The variation of VOC concentrations in different flight phases of long‐haul flights was the same as that of CO2 concentration except for the meal phase, which indicates the importance of cabin ventilation in diluting the gaseous contaminants, while the sustained and slow growth of the VOC concentrations during the cruising phase in short‐haul flights indicated that the ventilation could not adequately dilute the emission of VOCs. For the different categories of VOCs, the mean concentration during the cruising phase of benzene series, aldehydes, alkanes, other VOCs (detection rate > 50%), and carbonyls in long‐haul flights was 44.2 µg/m 3, 17.9 µg/m 3, 18.6 µg/m 3, 31.5 µg/m 3, and 20.4 µg/m 3  lower than those in short‐haul flights, respectively. Carbonyls and d‐limonene showed a significant correlation with meal service ( p  < 0.05). Unlike the newly decorated rooms or new vehicles, the inner materials were not the major emission sources in aircraft cabins. Practical Implications. The on‐board measurements of 56 flights enrich the VOC database of cabin environment, especially for carbonyls. The literature review of carbonyls in the past 20 years contributes to the understanding the current status of cabin air quality (CAQ). The analysis of VOC concentration variation for different flight phases, flight duration, and aircraft age lays a foundation for exploring effective control methods, including ventilation and purification for cabin VOC pollution. The enriched VOC data is helpful to explore the key VOCs of aircraft cabin environment and to evaluate the acute/chronic health exposure risk of pollutants for passengers and crew members.